Evaluation of cytochrome P450 inductions by anti-epileptic drug oxcarbazepine, 10-hydroxyoxcarbazepine, and carbamazepine using human hepatocytes and HepaRG cells. (1st September 2016) - Sugiyama, Ikuo; Murayama, Norie; Kuroki, Ayaka; Kota, Jagannath; Iwano, Shunsuke; Yamazaki, Hiroshi; Hirota, Takashi
Abstract: Anti-epileptic drug oxcarbazepine is structurally related to carbamazepine, but has reportedly different metabolic pathway. Auto-induction potentials of oxcarbazepine, its pharmacologically active metabolite 10-hydroxyoxcarbazepine and carbamazepine were evaluated by cytochrome P450 (CYP) 1A2, CYP2B6 and CYP3A4 mRNA levels and primary metabolic rates using human hepatocytes and HepaRG cells. For the CYP1A2 the induction potential determined as the fold change in mRNA levels was 7.2 (range: 2.3–11.5) and 10.0 (6.2–13.7) for oxcarbazepine and carbamazepine, respectively, while 10-hydroxyoxcarbazepine did not induce. The fold change in mRNA levels for CYP2B6 was 11.5 (3.2–19.3), 7.0 (2.5–10.8) and 14.8 (3.1–29.1) for oxcarbazepine, 10-hydroxyoxcarbazepine and carbamazepine, respectively. The fold change for CYP3A4 induction level by oxcarbazepine, 10-hydroxyoxcarbazepine and carbamazepine was 3.5 (1.2–7.4), 2.7 (0.8–5.7) and 8.3 (3.5–14.5), respectively. The data suggest lower induction potential of oxcarbazepine and 10-hydroxyoxcarbazepine relative to carbamazepine. The results in HepaRG cells showed similar trend as the human hepatocytes. After incubation for 72 h in hepatocytes and HepaRG cells, auto-induction was evident for only carbamazepine metabolism. The 10-keto group instead of double bond at C10 position is evidently a determinant factor for limited auto-induction of P450 enzymes by oxcarbazepine.